Linseed: A promising option for crop diversification, intensification, and income generation - Verma, Harendra; Pongen, Shisamen; Kalita, H (Indian Farming, 2024)
The North-Eastern Hill (NEH) region of India, characterized by its varied agro-climatic conditions, provides a distinctive prospect for cultivating linseed (Linum usitatissimum). Recognized for its conventional oilseeds, the region demonstrates notable potential for expanding linseed cultivation, given its adaptability and ability to yield both oil and fibre. Linseed can be a good option for cropdiversification enhancing cropping intensity by utilizing rice fallow land in the NEH region. Despite occupying only 5.6% of the cultivated area, oilseed cultivation in the NEH region shows promise for enhanced productivity, exemplified by linseed yielding 721.96 kg/ha in 2019-20. The diverse significance of linseed, stemming from its versatility and broad applications, including industrial and medicinal uses, positions it as a valuable crop and a compelling opportunity for increased cultivation in the NEH region.